Epistemologi Al Jabiri: Kontekstualisasi Perkembangan Hukum Islam di Masyarakat - Maula, Nanda Lia Roiya; Ats Tsaqofi, Atho' (Maliki Interdisciplinary Journal, 2024)
Epistemology refers to the study of knowledge and how it is acquired and validated. In the context of Al-Jabiri, he is known for his critical thinking regarding the Arab-Islamic intellectual tradition and his efforts to reform Islamic thought through a more rational and contextual approach. Al-Jabiri strives to renew Islamic legal thought to make it more relevant and responsive to the dynamics of contemporary society. This article explores Al-Jabiri's contributions to the reform of Islamic legal thought and its development in society. This research uses qualitative research, namely library research, which collects information and data using various kinds of material that can be accessed in the literature. The results of this study show that the development of Islamic law in society applies the epistemology of Islamic thought advocated by Muhammad Abid Al-Jabiri. This epistemology consists of three types: bayani, irfani, and burhani, each with concepts that produce various impacts and solutions to contemporary issues.